Chromosome Bands Induced in Human and Syrian Hamster Cells by Chemical Carcinogens - DiPaolo, J. A. (Nature Publishing Group, 1974)
After 24 hours of treatment of human peripheral leucocyte cultures or Syrian hamster embryonic secondary cultures with some known chemical carcinogens at concentrations that produce transformation in vitro of hamster cells, the chromosomes of both types of cells exhibited typical G banding. Chromosome bands did not result with urethane, a compound which does not produce cytotoxicity or cause transformation by direct exposure of cells. Non-carcinogenic chemicals which do not inhibit cell multiplication also failed to produce bands. Cytogenetic analysis following removal of the carcinogens from the cultures indicated non-banded uniformly stained chromosomes. It is concluded that metaphases with chromosome bands are more likely to be the result of nonspecific toxicity rather than being related to the carcinogenic properties of the chemicals. IMAGES: